2004
DOI: 10.1152/jn.01007.2003
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Multiphoton Microscopy of Deep Brain Tissue

Abstract: Although fluorescence microscopy has proven to be one of the most powerful tools in biology, its application to the intact animal has been limited to imaging several hundred micrometers below the surface. The rest of the animal has eluded investigation at the microscopic level without excising tissue or performing extensive surgery. However, the ability to image with subcellular resolution in the intact animal enables a contextual setting that may be critical for understanding proper function. Clinical applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
355
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 423 publications
(364 citation statements)
references
References 22 publications
4
355
1
4
Order By: Relevance
“…The introduction of multiphoton microscopy promises significant progress in in situ even in vivo investigation of tissue microcomponent with high precision and contrast (Brakenhoff et al, 1996;König et al, 1996;Zipfel et al, 2003a;Levene et al, 2004;Diaspro et al, 2005;Wang et al, 2005b). Based on this technique, visualization of the intracellular mitochondria (Barzda et al, 2005) and quantification of intracellular serotonin (Maiti et al, 1997) and NAD(P)H (Patterson et al, 2000) have been reported.…”
Section: Corneal 2-photon Excitation Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of multiphoton microscopy promises significant progress in in situ even in vivo investigation of tissue microcomponent with high precision and contrast (Brakenhoff et al, 1996;König et al, 1996;Zipfel et al, 2003a;Levene et al, 2004;Diaspro et al, 2005;Wang et al, 2005b). Based on this technique, visualization of the intracellular mitochondria (Barzda et al, 2005) and quantification of intracellular serotonin (Maiti et al, 1997) and NAD(P)H (Patterson et al, 2000) have been reported.…”
Section: Corneal 2-photon Excitation Imagingmentioning
confidence: 99%
“…Dendrites and spines can be imaged to study the alteration in their shape and size. The changes in axonal morphology of deep brain tissues were acquired through imaging of the activity of neuronal populations (Brecht et al, 2004;Levene et al, 2004;Nitsch et al, 2004;Chia & Levene, 2009). In particular, the cortical astrocytes were imaged in the intact mouse brain (Tian et al, 2006).…”
Section: Further Uses Of Multiphoton Excitation Imaging In Tumourous mentioning
confidence: 99%
“…Like other multi-photon techniques [10][11][12][13][14][15][16][17][18], THG not only enables the recording of label-free images of unfixed 3D volumes of tissue [1][2][3][4][5][6][7][8][9][10] free from spatial distortion artifacts inherent to histopathology, but also potentially allows feedback on the nature of the tissue, i. e. whether it is healthy or tumorous, to the surgeon during surgery, as the relative speed of the imaging modalities approaches 'real' time, and no preparation steps of the tissue are required [5,6,[19][20][21][22][23]. THG was shown recently to yield label-free images of ex-vivo human tumor tissue of histopathological quality, in real-time [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that multiple-spectra QDs can be used to achieve coincident tracking of multiple tumor cells in vivo using fluorescence emission-scanning microscopy (Gao et al, 2004;. In the central nervous system, microangiography of deep brain blood vessels and nonspecific labeling of brain cells has been achieved following QD injection into arterial blood (Levene et al, 2004;Voura et al, 2004).…”
Section: Introductionmentioning
confidence: 99%